2018
DOI: 10.1126/scisignal.aar7921
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression kinetics governs stimulus-specific decoration of the Salmonella outer membrane

Abstract: Lipid A is the innermost component of the lipopolysaccharide (LPS) molecules that occupy the outer leaflet of the outer membrane in Gram-negative bacteria. It is recognized by the host immune system and targeted by cationic antimicrobial compounds. In Salmonella enterica serovar Typhimurium, the phosphates of lipid A are chemically modified by enzymes encoded by targets of the transcriptional regulator PmrA. These modifications increase resistance to the cationic peptide antibiotic polymyxin B by reducing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…Such compartmentspecific down regulation has been observed previously in various infection models. 25,[80][81][82] S. Tm requires TTSS-1 and flagella (composed of flagellin subunits) for the initial colonization and establishment of gut infection. 16,72 Especially for invasion of IECs, which strongly express Naip1, 2, 5, 6, and Nlrc4 ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Such compartmentspecific down regulation has been observed previously in various infection models. 25,[80][81][82] S. Tm requires TTSS-1 and flagella (composed of flagellin subunits) for the initial colonization and establishment of gut infection. 16,72 Especially for invasion of IECs, which strongly express Naip1, 2, 5, 6, and Nlrc4 ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we observed that tris -phosphorylated lipid A was not enhanced in lpxT overexpressing cells, as shown by MALDI-TOF MS, probably because of feedback regulation mechanisms that limit LpxT activity when the lpxT gene is induced [ 17 , 18 , 21 ]. This result rules against the hypothesis that LpxT toxicity may be due to hyperphosphorylation of lipid A. Contextually, an LpxT H190A variant devoid of catalytic activity [ 19 ] is even more detrimental for growth, at least in solid medium, than the wt protein.…”
Section: Discussionmentioning
confidence: 90%
“…In E. coli , LpxT is encoded by the lpxT gene and it is subject to a complex regulation. Indeed, lpxT transcription initiation is downregulated at 37–42 °C vs. 30 °C, in stationary phase and at high Mg 2+ concentration [ 15 , 17 , 18 ]. The lpxT mRNA stability is also modulated, as the mRNA is quickly destabilized after a temperature upshift from 30 to 37 °C [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…We took a reductive approach to quantify the impact of macAB genotype on antimicrobial peptide resistance. We reasoned that the contribution of MacAB to antimicrobial peptide resistance could be obscured in vitro by the profound PhoP-induced membrane modifications that dramatically slow antimicrobial peptide interactions with the cell envelope [ 59 ]. Furthermore, the constitutively expressed AcrAB-TolC pump effluxes a wide variety of compounds and can mask the contributions of other efflux pumps like MacAB during in vitro tests of antibiotic resistance [ 34 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Typhimurium replication in macrophages [ 38 , 56 ], a niche where PhoP/Q signaling is active and important for Salmonella survival [ 55 , 61 ]. In addition to the different Salmonella isolates used across studies, our results suggesting PhoP promotes macAB transcription may arise from differences in experimental conditions, the importance of regulatory kinetics such as PhoP turnover [ 38 ], changes in ribosomal RNA levels in response to low magnesium [ 84 ], or coordinated activity with other transcriptional regulators [ 59 ]. We conclude that PhoP-inducing signals generally serve to maximize macAB transcription in Salmonella .…”
Section: Discussionmentioning
confidence: 99%